Mathematical Model of Silicon Oxidation in Microelectronics - V. A. Bondarev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper involves analytical solutions and formulae for determination of the oxide film thickness in the silicon oxidation while using nitride mask. Calculations are based on solutions of a three-dimensional diffusion equation and new mathematical functions that are firstly defined by the author. Suitable analytical and numerical solutions based on the diffusion equation have not yet been obtained